TECHNOLOGICAL METHODS OF CONSTRUCTION MILITARY ENGINEERING FACILITIES RUBAS FORTIFICATION VI C. (EAST CAUCASUS) - Gmyra, Ludmila Borisovna (History, Archeology and Ethnography of the Caucasus, 2022)
The article reviews building techniques, used for constructing a monumental fortification of the 6th century, erected in the river-valley of Rubas, near the village of Kommuna, Derbent region of the Republic of Dagestan.  The site includes six objects different in layout and construction, connected with building junctions into a single object – a construction of arched type, Wall 1, Long wall 2, Stepped structure 6, Wall 3, Platform 5. Analysis of the excavation material shows that the technology of their building was due to the functional purpose of these objects. Moreover, each of the architectural structures was built with the use of unique building techniques, variety of masonry, as well as the sizes of stone blocks and plates. The aim of the research is to conduct the analysis of the technological methods of constructing multi-type military-engineering fortifications; to determine the links of technological methods with the object’s functional purposes; to determine the level of development of construction engineering and architecture in the Peri-Caspian region in the era of the Great Migration of Peoples and the significance of this site as a military-defensive construction. The research methodology includes a detailed analysis of technological methods for the construction of military engineering structures; carrying out the classification of methods for the construction of defensive objects and the system of laying stone structures; analysis of building materials used in the construction of structures. The analysis of the excavation materials of the Rubas fortification shows that, according to the technology of construction, this object is close to the Derbent defensive complex of the middle 6th century (large stone blocks; massiveness of structures; the use of “opus quadratum” masonry; the presence of a bonding lime mortar, etc.). According to the main indicators (monumentality and functional orientation), this structure belongs to a series of barriers in the Western Peri-Caspian, built by Persia with the financial assistance of Byzantium in the era of the Great Migration of Peoples, typologically and chronologically similar to Derbent.
Keywords: the Rubas fortification; East Caucasus; river valley of Rubas; Wall 1; Wall 2; Stepped structure 6; Wall 3; Platform 5; building techniques; masonry system; constructive building techniques; composition of building materials